Using hydrogel and clay to improve the water status of seedlings for dryland restoration - Chirino, Esteban; Vilagrosa, Alberto; Vallejo, V. Ramón (Plant and Soil, 2011)
In dryland ecosystems, post-transplant water stress produces high seedling mortality after the first summer following outplanting. Our aim was to assess the effects of clay and hydrogel, both on the water holding capacity of the growing media and on various morphological and physiological characteristics of Quercus suber seedlings in the nursery and, subsequently, during the first 2 years in the field. Quercus suber L. seedlings were grown in four types of growing media: CS (Control growing media, standard mixture of limed peat and coconut peat, 1:1 v/v ratio), SC-10 (CS mixed with sepiolite clay at 10% v/v) and HS (CS mixed with hydrogel Stockosorb® K-400 at two doses, 0.7 and 1.5% w/w). HS-1.5 showed the best results, increasing the water holding capacity of the root plug, improving seedling water status and increasing seedling survival in the field. SC-10 showed an intermediate effect on seedling response in the field. Mixing hydrogel with a peatbased growing medium to form root plugs is a suitable technique for cultivating species to be planted in areas with a strong water deficit. This technique reduces posttransplant water stress in seedlings during their first months in the field and contributes to improve forestrestoration methods in dryland ecosystems.
Keywords: carbon isotope composition; plant stock quality; Quercus suber; substrate; Water availability

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens